Therapeutic Potential of Drugs Targeting Pathophysiology of Intracerebral Hemorrhage: From Animal Models to Clinical Applications - Liao, Kuo-Hsing; Sung, Chih-Wei; Huang, Ya-Ni; Li, Wei-Jiun; Yu, Po-Chuan; Wang, Jia-Yi (Current Pharmaceutical Design, 2017)
Background: Intracerebral hemorrhage (ICH) is one of the most common forms of cerebral hemorrhage, the morbidity and death of ICH is high worldwide. ICH can be spontaneous or caused by hypertension, coagulopathy, angiopathy, head trauma, bleeding disorders, tumors, or drug usage. ICH is the most serious and least treatable form of hemorrhagic stroke, with rapidly increasing hematoma size and often resulting in significant brain injury and long term neurological deficits. Surgical hematoma evacuation remains controversial. The currently therapy is mainly supportive with limited benefit. New therapeutic approaches are desperately needed. Methods: In this review, we provide an overview of the published literature concerning the pathophysiology leading to the ongoing neurologic damage, Emerging information of the physio-pathologic mechanisms of injury that occur after ICH is available from current animal models. Ideal therapeutic strategies should target on the pathophysiology of ICH. This review summarizes the recent advances in developing pharmaceutical agents in terms of therapeutic targets and effects in pre-clinical and clinical studies. Results: Recent animal and clinical studies have provided important information about the parallel and sequential deleterious mechanisms underlying ICH-induced brain injury and pharmacological agents targeting on these mechanisms. Neuroscientists have paid more attention to novel drug development that target on antioxidants, antiinflammatory, and anti-apoptosis for neuroprotection after ICH. Conclusion: Although ICH remains without an approved treatment proven to decrease morbidity and mortality, notable advances in the understanding of ICH pathophysiology and new drug development have been made in the last decade.
Keywords: therapeutics